E-Learning: Challenges of Utilizing Weblog in EFL learning Environment - Anees Alnajjar,; Mohmmed Shormani,; Noman Musleh Musaed AL-Sayadi, (International Journal of Linguistics Studies, 2024)
E-learning can enhance learners’ collaboration and interaction synchronously or asynchronously via utilizing Web 2.0 platforms. Yet blog utility in EFL contexts could have serious challenges. So, this study explored the most serious challenges perceived by Yemeni EFL Level-II students, English Department, Faculty of Arts, Ibb University, in 2023-2024 after a semester-long blogging. A quasi-experimental research design was used with an experimental group of 5 males and 10 females who utilized blog for posting their writing assignments and a controlling group of 3 males & 12 females who did so traditionally. A Survey Students Open-ended Questionnaire and Students Semi-Structured Interviews were used for collecting the data. The posttest findings revealed that experimental group performed better than the controlling group confirming that blog substantially developed students’ writing skills. Also, the interview findings showed highly-perceived learning situation, blogging situation, and students challenges. The findings can avoid Yemeni EFL teachers contingent jump-start blogging pitfalls. Further